P PENERAPAN PROGRAM KKN MBKM KIMIA ASIK UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS X DI SMAN 2 KOTA BENGKULU (Andromeda: Jurnal Pengabdian Masyarakat Rafflesia, 2024)
The MBKM KKN program entitled "Fun Chemistry" was implemented at SMAN 2 Bengkulu City with the aim of increasing the interest of class X students in chemistry lessons through ice cream making practicums. The methods used include lectures, discussions, and practices. Students learn chemical principles such as physical changes, temperature, emulsion formation, and crystallization through conventional methods. The results of the questionnaire showed a significant increase in student interest in learning after this activity, especially in understanding the application of chemistry in everyday life. Teachers also gave positive responses to this interactive approach. This program has succeeded in changing the paradigm of chemistry learning from difficult and boring to interesting and relevant. With practical experiments, this program not only improves students' understanding of chemical concepts, but also fosters their curiosity and involvement in the learning process.